PERAN DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM MENCEGAH KEKERASAN DI KOTA PONTIANAK - Hemafitria Hemafitria; Erna Octavia; Agustin Markononi (IKIP PGRI PONTIANAK, 2023)
This study aims to determine the role of the Department of Population Control and Family Planning, Women's Empowerment and Child Protection in preventing violence in the city of Pontianak. the method used is a qualitative method with descriptive analysis. data collection tools using observation guides, interviews and documentation. data analysis technique uses reduction, presentation, and verification. The results of this study indicate that the forms of violence that occur to women and children are domestic violence, sexual violence, sexual abuse, and trafficking. The obstacles experienced are the lack of human resources or employees, not wanting to report, and people who don't care. Efforts made by the Department of Population Control and Family Planning, Women's Empowerment and Child Protection in preventing violence in the city of Pontianak are to provide socialization, provide assistance, and legal protection.